Covid‐19 health crisis and lockdown associated with high level of sleep complaints and hypnotic uptake at the population level - Beck, Francois; Léger, Damien; Fressard, Lisa; Peretti‐Watel, Patrick; Verger, Pierre (Journal of sleep research, 2021)
The Covid‐19 pandemic has disrupted the habits of billions of people around the world. Lockdown at home is mandatory, forcing many families, each member with their own sleep–wake habits, to spend 24 hr a day together, continuously. Sleep is crucial for maintaining immune systems and contributes deeply to physical and psychological health. To assess sleep problems and use of sleeping pills, we conducted a cross‐sectional study of a representative sample of the general population in France. The self‐reported sleep complaint items, which covered the previous 8 days, have been used in the 2017 French Health Barometer Survey, a cross‐sectional survey on various public health issues. After 2 weeks of confinement, 74% of the participants (1,005 subjects) reported trouble sleeping compared with a prevalence rate of 49% in the last general population survey. Women reported more sleeping problems than men, with greater frequency or severity: 31% vs. 16%. Unusually, young people (aged 18–34 years) reported sleep problems slightly more frequently than elderly people (79% vs. 72% among those aged 35 or older), with 60% of the younger group reporting that these problems increased with confinement (vs. 51% of their elders). Finally, 16% of participants reported they had taken sleeping pills during the last 12 months, and 41% of them reported using these drugs since the lockdown started. These results suggest that the COVID crisis is associated with severe sleep disorders among the French population, especially young people.